The speech acts of persuasion: a case study of Pharmaceutical advertisement in selected Ghanaian media . - Agyakoma, Sarfo Mavis (KNUST, 2025)
A thesis submitted to the Department of English, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the award of Master Of Philosophy Degree In English Language